5-Hydroxy-3-phenyl-5-trifluoromethyl-4,5-dihydro-1H-pyrazole - Asiri, Abdullah M. (International Union of Crystallography, 2011)
The five-membered dihydropyrazole ring in the title compound, C(10)H(9)F(3)N(2)O, is approximately planar (r.m.s. deviation 0.111 Å for all non-H atoms) and its phenyl substituent is aligned at an angle of 14.7 (2)°. Adjacent molecules are linked by N—H⋯O and O—H⋯N hydrogen bonds, generating ribbons running along the b axis of the monoclinic unit cell.